2014
DOI: 10.1002/14651858.cd006732.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for improving the adoption of shared decision making by healthcare professionals

Abstract: It is uncertain whether interventions to improve adoption of SDM are effective given the low quality of the evidence. However, any intervention that actively targets patients, healthcare professionals, or both, is better than none. Also, interventions targeting patients and healthcare professionals together show more promise than those targeting only one or the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
136
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(139 citation statements)
references
References 96 publications
3
136
0
Order By: Relevance
“…This finding is consistent with prior literature evaluating the effect of decision aids. 1, 2 Indeed, the use of SDM and decision aids (i.e., decision support and information about treatment options) allows patients to become more confident in their choice to have, or not have, surgery 30, 31 which then promotes health and well-being both during and following the decision-making process and operation. 32, 33 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with prior literature evaluating the effect of decision aids. 1, 2 Indeed, the use of SDM and decision aids (i.e., decision support and information about treatment options) allows patients to become more confident in their choice to have, or not have, surgery 30, 31 which then promotes health and well-being both during and following the decision-making process and operation. 32, 33 …”
Section: Discussionmentioning
confidence: 99%
“…SDM by definition involves a collaborative process that creates a partnership between the doctor and patient. 1, 38 Kennedy et al 39 found that surgery rates were lowest when patients received both a decision aid and an interview, as opposed to a decision aid in isolation. As such, perhaps a distinction between information-based decision-making (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both case studies, we learned that a health system that lacks cultural norms such as 'patient-centred approach' or 'shared-decision making' (Légaré et al, 2014) deters providers in engaging in conversations about changing their clients' smoking behaviour.…”
Section: Outer Settingsmentioning
confidence: 99%
“…There are numerous types of interventions for facilitating SDM that target the healthcare team, the patient, or the public [8]. However, patient decision aids remain the most widely known effective strategy [9].…”
Section: Introductionmentioning
confidence: 99%